Comparative efficacy of combined and single neuromuscular electrical stimulation and traditional swallowing training for neurogenic dysphagia: a network meta-analysis - Wang, Shuxuan; Shi, Zhenyu; Wu, Tingting; Li, Chong; Huang, Chuchu; Sun, Di (Frontiers in Neurology, 2025)
ObjectiveThis study aims to compare the efficacy of combined and single neuromuscular electrical stimulation (NMES), and traditional swallowing training (TST) for neurogenic dysphagia through a network meta-analysis (NMA).MethodsThis meta-analysis has been prospectively registered on the PROSPERO (Registration number: CRD42025643351). Electronic databases, including Embase, PubMed, Web of science and the Cochrane Library, were searched up to March 1, 2025. All published randomized controlled trials (RCTs) comparing combined and/or single neuromuscular electrical stimulation with traditional swallowing therapy for the treatment of patients with neurogenic dysphagia were included. A network meta-analysis using STATA software synthesized data and ranked treatments by efficacy. The outcome measures included the Functional Oral Intake Scale (FOIS), Standardized Swallowing Assessment (SSA), Penetration-Aspiration Scale (PAS) and clinical efficacy (CE).ResultsTwenty-two RCTs with a total sample size of 1,265 cases were ultimately included. The findings suggest that NMES combined with other therapies is more effective than single NMES or traditional swallowing therapy for patients with neurogenic dysphagia, demonstrating a higher clinical efficacy rate. Among the combined therapies, the integration of NMES with transcranial direct current stimulation (tDCS) and TST demonstrated the highest efficacy in improving FOIS scores and enhancing swallowing function [surface under cumulative ranking curve values (SUCRCV): 95.3%, standardized mean difference (SMD): 1.15, 95% confidence interval (CI): 0.34, to 1.97]. Additionally, NMES combined with acupuncture showed the most significant reduction in SSA scores (SUCRA: 87.6%, SMD: −1.49, 95% CI: −2.48 to −0.49). Furthermore, the combination of NMES combined with effortful swallowing (ES) and TST exhibited the most pronounced effects in lowering PAS scores and preventing aspiration (SUCRA: 81.2%, SMD: −1.06, 95% CI: −1.82 to −0.31).ConclusionsRanking probabilities indicated that combined therapy had the highest likelihood of being the most effective intervention. However, large-scale, multi-center, high-quality studies are essential to further validate this conclusion.